2019
DOI: 10.1093/cid/ciz195
|View full text |Cite
|
Sign up to set email alerts
|

Postnatally Acquired Zika Virus Disease Among Children, United States, 2016–2017

Abstract: Background The clinical findings among children with postnatally acquired Zika virus disease are not well characterized. We describe and compare clinical signs and symptoms for children aged <18 years. Methods Zika virus disease cases were included if they met the national surveillance case definition, had illness onset in 2016 or 2017, resided in a participating state, and were reported to the Centers for Disease Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 15 publications
2
22
1
Order By: Relevance
“…12,13 Because Zika manifests differentially across childhood, and standard case definitions include clinical findings rarely observed in our large paediatric population, symptomatic ZIKV infection could manifest differently across the lifespan. This hypothesis is supported by the age-varying prevalence of various Zika clinical findings, observed in comparisons of younger children with older children (in our study and others) 8,9 and in comparisons of children with adults. 9 A comparison of Zika clinical findings in paediatric and general population studies provides further evidence in support of this hypothesis (appendix pp 28-30).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…12,13 Because Zika manifests differentially across childhood, and standard case definitions include clinical findings rarely observed in our large paediatric population, symptomatic ZIKV infection could manifest differently across the lifespan. This hypothesis is supported by the age-varying prevalence of various Zika clinical findings, observed in comparisons of younger children with older children (in our study and others) 8,9 and in comparisons of children with adults. 9 A comparison of Zika clinical findings in paediatric and general population studies provides further evidence in support of this hypothesis (appendix pp 28-30).…”
Section: Discussionsupporting
confidence: 88%
“…This hypothesis is supported by the age-varying prevalence of various Zika clinical findings, observed in comparisons of younger children with older children (in our study and others) 8,9 and in comparisons of children with adults. 9 A comparison of Zika clinical findings in paediatric and general population studies provides further evidence in support of this hypothesis (appendix pp 28-30). Specifically, general population Zika studies report a higher prevalence of arthralgia, myalgia, conjunctival involve ment, headache, periarticular oedema, and gastrointestinal and respiratory clinical findings than do studies of paediatric Zika.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…17,18 Previous studies found that rash and fever were the two most common symptoms in pediatric ZIKV cases. 19,20 However, rash was the only symptom that was significantly more common in children with ZIKV than those without ZIKV in our study. All pediatric ZIKV cases in our study had lower peak temperature than pediatric non-ZIKV cases.…”
Section: Discussioncontrasting
confidence: 52%